Construction of Anterior Hemi‐Corneal Equivalents Using Nontransfected Human Corneal Cells and Transplantation in Dog Models. Issue 11 (16th June 2017) - Xu, Bin; Song, Zhan; Fan, Tingjun
Abstract: Tissue‐engineered human anterior hemi‐cornea (TE‐aHC) is a promising equivalent for treating anterior lamellar keratopathy to surmount the severe shortage of donated corneas. This study was intended to construct a functional TE‐aHC with nontransfected human corneal stromal (ntHCS) and epithelial (ntHCEP) cells using acellular porcine corneal stromata (aPCS) as a carrier scaffold, and evaluate its biological functions in a dog model. To construct a TE‐aHC, ntHCS cells were injected into an aPCS scaffold and cultured for 3 days; then, ntHCEP cells were inoculated onto the Bowman's membrane of the scaffold and cultured for 5 days under air‐liquid interface condition. After its morphology and histological structure were characterized, the constructed TE‐aHC was transplanted into dog eyes via lamellar keratoplasty. The corneal transparency, thickness, intraocular pressure, epithelial integrity, and corneal regeneration were monitored in vivo, and the histological structure and histochemical property were examined ex vivo 360 days after surgery, respectively. The results showed that the constructed TE‐aHC was highly transparent and composed of a corneal epithelium of 7–8 layer ntHCEP cells and a corneal stroma of regularly aligned collagen fibers and well‐preserved glycosaminoglycans with sparsely distributed ntHCS cells, mimicking a normal anterior hemi‐cornea (aHC). Moreover, both ntHCEP and ntHCS cells maintained positive expression of their marker and functional proteins. After transplantation into dog eyes, the constructed TE‐aHC acted naturally in terms of morphology, structure and inherent property, and functioned well in maintaining corneal clarity, thickness, normal histological structure, and composition in dog models by reconstructing a normal aHC, which could be used as a promising aHC equivalent in corneal regenerative medicine and aHC disorder therapy.